A systematic literature review: the effect of date palms (phoenix dactylifera) toward breast cancer MCF-7 cell line. - Abdullah, Teo Wee Siang@Aariz Daniel Teo; Zainol, Nur Zainatul Nadra; Mat Nayan, Nadirul Hasraf; Muhammad, Norhayati (2021)
Breast cancer is most significant diagnosed cancer in women that approximately 2.1 millions women were diagnosed with breast cancer and caused 627,000 deaths worldwide in 2018 based on Press Release 2018 from International Agency for Research on Cancer in World Health Organization (WHO) [1]. Phoenix dactylifera or in common name, date palm has become one of the choices to avoid breast cancer. The various types of extract methods on difference parts of P.dactylifera against breast cancer cell line or known as Michigan Cancer Foundation-7 (MCF-7) were widely discussed in previous research articles. However, it was lack of systematically review on effect of the parts of P.dactylifera against breast cancer or MCF-7. PRISMA method was applied on Scopus and Science Direct databases and resulted on six parts of the P.dactylifera’s extracts. For future direction, it was encouraged to apply different standard systematic review methods and extra databases.